The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1002/cjce.5450820311
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Internal and External Mixer Spargers in a Laboratory De‐inking Flotation Column

Abstract: Paper recycling is assuming increased importance in response to growing concerns over waste disposal and conservation of natural resources. The paper recycling process aims to remove contaminants while retaining the valuable fi bers. This is accomplished through a variety of separation processes including screening, cycloning, fl otation and washing.Today, fl otation dominates the removal of printing inks from recycled paper. A typical composition of a feed pulp is given in Table 1. De-inking is a reverse fl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…For instance, the operation of a flotation column with two phases (water–gas) has resulted in the clarification of many unknown factors regarding the individual phases . Column flotation reactors in countercurrent mode have been introduced into a number of deinking operations . Column trials indicated that, at a few minutes retention time, over 70% of macrostickies and wax from rejects of a typical pulp deinking plant could be removed .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the operation of a flotation column with two phases (water–gas) has resulted in the clarification of many unknown factors regarding the individual phases . Column flotation reactors in countercurrent mode have been introduced into a number of deinking operations . Column trials indicated that, at a few minutes retention time, over 70% of macrostickies and wax from rejects of a typical pulp deinking plant could be removed .…”
Section: Introductionmentioning
confidence: 99%
“…Despite its versatility and apparent simplicity, froth flotation is governed by complex physicochemical and hydrodynamic phenomena which depend on pulp slurry/process chemicals composition [6,14,15] and on gas sparger [16,17] and flotation cell design [18,19].…”
Section: Introductionmentioning
confidence: 99%